2017
DOI: 10.1039/c6cp07754d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on substituent and solvent effects for nanocubes formed with gear-shaped amphiphile molecules

Abstract: Gear-shaped amphiphile molecules (1) recently synthesized by Hiraoka et al. self-assemble into a hexameric structure, nanocubes (1), in 25% aqueous methanol due to a solvophobic effect. Here we have carried out molecular dynamic simulations to elucidate the stability of these hexameric capsules (1 and 2) in water, 25% aqueous methanol, and methanol. In all solvents, the 1 nanocubes are maintained for all trajectories. On the other hand, 2 was found to collapse for one trajectory in water and seven trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…3b ), suggesting a large distortion around the poles by the encapsulation of a rodlike or a large planar molecule with the longest side of 12 Å. This is consistent with the previous finding that the molecular meshing around the equator is stronger than that around the poles 40 , 41 . In every case, a further desymmetrization of the nanocube upon the complexation was not observed by 1 H NMR spectroscopy, indicating that the tumbling motion of the guest molecule(s) in the nanocube is much faster than the NMR timescale.…”
Section: Resultssupporting
confidence: 90%
“…3b ), suggesting a large distortion around the poles by the encapsulation of a rodlike or a large planar molecule with the longest side of 12 Å. This is consistent with the previous finding that the molecular meshing around the equator is stronger than that around the poles 40 , 41 . In every case, a further desymmetrization of the nanocube upon the complexation was not observed by 1 H NMR spectroscopy, indicating that the tumbling motion of the guest molecule(s) in the nanocube is much faster than the NMR timescale.…”
Section: Resultssupporting
confidence: 90%
“…In our previous study, we found that the nanocube has two main important interactions: the π − π stacking interactions between two 3-pyridyl groups and the CH−π interactions. 28 As GSA 2 lacks three p-tolyl methyl groups, stability of the 2 6 nanocube mainly depends on π−π interactions. Although the structure of the G@2 6 nanocube shown in Figure 7 is deformed from a cube, this distorted structure is weakly stabilized by the double π stacking interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Force field information is written in the ESI of our previous paper. 28 Water and methanol solvent molecules are assigned the Brerendsen's SPC/E model 29 and the AMBER ff99SB force field, 25 respectively. The SHAKE algorithm 30 was exploited to constrain bonds involved the hydrogen atoms.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The GSA monomer 1 has a hexaphenylbenzene core, in which three hydrophilic pyridyl groups and three hydrophobic methyl groups are introduced. The GSA monomers are molecularly dissolved in pure methanol, while they spontaneously form the nanocube in aqueous methanol. , Previous studies have demonstrated that the vdW, π-stacking, and CH−π interactions play a crucial role in the stability of the nanocube, particularly through meshing of the indented molecular surfaces of GSA monomers. , Very recently, it was also reported that the water-soluble nanocubes (obtained from the self-assembly of cationic GSA molecules in pure water) exhibit a high thermal stability beyond the boiling point of water …”
mentioning
confidence: 99%
“…10,11 Previous studies have demonstrated that the vdW, πstacking, and CH−π interactions play a crucial role in the stability of the nanocube, particularly through meshing of the indented molecular surfaces of GSA monomers. 13,14 Very recently, it was also reported that the water-soluble nanocubes (obtained from the self-assembly of cationic GSA molecules in pure water) exhibit a high thermal stability beyond the boiling point of water. 14 Understanding the self-assembly process of molecular systems remains a significant challenge for computer simulation.…”
mentioning
confidence: 99%